PENGARUH SELF-CONCEPT AKADEMIK TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS VI SEKOLAH DASAR SELAMA PANDEMI COVID-19 - Mohammad Archi Maulyda; Dyah Indraswati; Muhammad Erfan; Arif Widodo; Aisa Nikmah Rahmatih (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
This research aims to determine the influence of the academic self-concept on the independence of learning class VI students during the pandemic. Research in the background is a problem that many students lack self-reliance in learning at an elementary school education level, especially when online-based learning is enforced during the pandemic. In addition, when exams are many students who are unable to work on their own and ask a friend next to him when the exam is in progress. This research uses a quantitative-descriptive approach. This type of research is correlation research. The subject in this study amounted to 40 students. The variables studied are self-concept academic and self-learning independent students. Data is collected through the self-learning concept of academic and student self-reliance. From the analysis results using the correlation analysis of product-moment with the help of SPSS version 23.0, obtained R table results with N = 70 and α = 5%, is 0.235. While the Rcount obtained the magnitude of 0.769, then Rcountdown > Rtabel (0,769 > 0,235), meaning there is a positive and significant influence, consequently Ho rejected and Ha accepted. So, in conclusion "there is a positive and significant influence of the self-academic concept of learning Independence-class VI students". That means the higher the academic self-concept of students, the higher the independence of learning and vice versa when the self-academic concept is low then the student independence is low. Based on the results of the study students are expected to learn with self-awareness without the compulsion of parents or teachers and in learning not dependent on others. Teachers are expected to observe the students ' academic self-concept and strive to improve it so that students can have high self-reliance learning and can complete their study tasks perfectly.